Enhancing Antioxidant Properties of Ice Cream with Broken-Milled Riceberry Rice Extract - Srisukong, Amornrat; Yuyen, Yutthaya; Kiattiprajuksa, Suchaya; Pichaiyongvongdee, Suwanna; Itsarasook, Khwunjit; Phornphisutthimas, Somkiat (Journal of Food Health and Bioenvironmental Science, 2025)
This study investigated the potential of broken-milled Riceberry rice extract as a natural bioactive ingredient for ice cream enrichment. Extracts were prepared using ethanol-water solutions at various concentrations (10–50%), with 50% ethanol yielding the highest levels of anthocyanins (20.84 mg cyanidin-3-glucoside/100 g DW), total phenolics (143.15 mg GAE/100 g DW), and strong antioxidant activity (78.36% DPPH scavenging activity). High-performance liquid chromatography (HPLC) revealed a phenolic profile rich in vanillic, protocatechuic, and sinapic acids. The extract was freeze-dried and incorporated into ice cream at 0.5%, 1.0%, and 1.5% (w/w). Fortification significantly increased total phenolic content and antioxidant activity, with the 1.5% formulation reaching 84.97% DPPH scavenging activity. Physical characteristics such as viscosity and color were also affected, while pH remained stable. These results highlight the extract’s potential for use in functional frozen desserts, providing a sustainable way to valorize agricultural byproducts while enhancing nutritional quality.